In Vitro Gas Production and Rumen Degradability of Lactating Dairy Cow’s Rations Containing Three Different Grasses - Pramita, Melyndra Sonya; Soetanto, Hendrawan (Universitas Halu Oleo, 2022)
This research aimed to ascertain whether dwarf elephant grass (DEG) is compatible to substitute the common forages, viz. elephant grass (EG) and maize stover (MS) in the dairy cow rations (denote as R) using in vitro gas production (IVGP) technique. A completely randomized block design was applied to 4 feeding regimes and 3 replicates, viz. R1 consisted of 40% concentrate (C) + 30% MS + 30% EG; R2: 40% C + 30% MS + 30% DEG; R3: 40%C + 60% EG; and R4: 40% C + 60% DEG. The results showed that rations containing DEG improved both DM and OM degradabilities concomitant with increased in rumen efficiency of microbial protein synthesis (EMPS). Nevertheless, total and potential of gas production (GP) were higher in rations containing MS than other counterparts suggesting that there was a diverting usage of ROMD available for GP and EMPS. In conclusion, the use of DEG in dairy rations is recommended.